THE ANALYSIS OF TWO ESL/EFL WEBSITES: ENGLISHCLUB AND ACTIVITIES FOR ESL STUDENTS - Antonia Tefa; Flora Debora Floris (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
This study reviewed two well known ESL/EFL websites namely EnglishClub and Activities for ESL Students using the website evaluation framework proposed by Hasan and Abuelrub (2011). The writers found that Activities for ESL Students met 79.92% of the website evaluation criteria with 211 of the total score; while EnglishClub met 79.54% of the website evaluation criteria with 210 of the total score. Thus there was no significant difference between these two websites. Both EnglishClub and Activities for ESL Students are good for ESL/EFL learners